Fat Embolism Syndrome Complicated by Acute Pulmonary Thromboembolism after Bilateral femoral shaft Fractures: Two Nightmares in the Same Patient - Aamir Shafi; Jawhar Ul Islam; Wani Abdul Ahad; Aariba Zahoor (Dr. Annil Mahajan, 2023)
Fat embolism syndrome is an uncommon but fatal complication usually in orthopaedic trauma especially after a long bone fracture. A high level of suspicion should be kept in mind when a patient of long bone fracture develops hypoxia, confusion or rash in the absence of infection and other causes of ARDS. Concomitant FES and pulmonary thromboembolism is a more rarer entity in comparison to FES and pulmonary thromboembolism separately. There are few cases reported in literature wherein patients developed concomitant FES and pulmonary embolism. Almost in all cases fat embolism syndrome and pulmonary embolism occurred either simultaneously or pulmonary thromboembolism was complicated by FES. We report a case wherein patient initially developed FES pre operatively which was later on complicated by acute pulmonary thromboembolism in the post operative period.